Production and Optimization of Biosurfactant Properties Using Candida mogii and Licuri Oil (Syagrus coronata) - Peterson F. F. da Silva; Renata R. da Silva; Leonie A. Sarubbo; Jenyffer M. C. Guerra (Foods)
Optimizing biosurfactant (BS) production is key for sustainable industrial applications. This study investigated BS synthesis by Candida mogii using licuri oil, a renewable carbon source rich in medium-chain fatty acids. Process optimization was conducted via central composite design (CCD), adjusting concentrations of licuri oil, glucose, NH4NO3, and yeast extract. The predictive model achieved an R2 of 0.9451 and adjusted R2 of 0.8812. Under optimized conditions, C. mogii lowered water surface tension from 71.04 mN·m−1 to 28.66 mN·m−1, with a critical micelle concentration (CMC) of 0.8 g·L−1. The biosurfactant displayed high emulsification indices, exceeding 70% for canola, licuri, and motor oils, suggesting strong potential as an industrial emulsifier. FTIR and NMR analyses confirmed its glycolipid structure. Bioassays showed no toxicity to Lactuca sativa seeds, ensuring environmental safety, while antimicrobial tests demonstrated efficacy against Staphylococcus aureus and Escherichia coli, indicating its suitability as a biocidal agent. This work positions C. mogii BS from licuri oil as a promising alternative for bioremediation, biotechnology, and antimicrobial uses.